Mechanism of action of novel synthetic dodecapeptides against Candida albicans - Maurya, Indresh Kumar; Thota, Chaitanya Kumar; Sharma, Jyotsna; Tupe, Santosh Genba; Chaudhary, Preeti; Singh, Manoj Kumar; Thakur, Indu Shekhar; Deshpande, Mukund V.; Prasad, Rajendra; Chauhan, Virander Singh (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Three de novo designed low molecular weight cationic peptides (IJ2, IJ3 and IJ4) containing an unnatural amino acid alpha,beta-didehydrophenylalanine (APhe) exhibited potent antifungal activity against fluconazole (FLC) sensitive and resistant clinical isolates of Candida albicans as well as non-albi cans and other yeast and filamentous pathogenic fungi. In the present study, their synthesis, susceptibility of different fungi and the mechanism of anti-candidal action have been elucidated. Methods: The antimicrobial peptides (AMPs) were synthesized by solid-phase method and checked for antifungal activity against different yeasts and fungi by broth microdilution method. Anti-candidal mode of action of the peptides was investigated through detecting membrane permeabilization by confocal microscopy, Reactive Oxygen Species (ROS) generation by fluorometry, apoptosis and necrosis by flow cytometry and cell wall damage using Scanning and Transmission Electron Microscopy. Results and conclusions: The MIC of the peptides against C. albicans and other yeast and filamentous fungal pathogens ranged between 3.91 and 250 mu M. All three peptides exhibited effect on multiple targets in C. albi cans including disruption of cell wall structures, compromised cell membrane permeability leading to their enhanced entry into the cells, accumulation of ROS and induction of apoptosis. The peptides also showed synergistic effect when used in combination with fluconazole (FLC) and caspofungin (CAS) against C. albi cans. General significance: The study suggests that the AMPs alone or in combination with conventional antifungals hold promise for the control of fungal pathogens, and need to be further explored for treatment of fungal infections. (C) 2013 Elsevier By. All rights reserved.
Keywords: Antifungal peptide; Antimicrobial peptide (AMP); Apoptosis; Candida albicans; Reactive Oxygen Species (ROS)

Fungal cell membrane-promising drug target for antifungal therapy - Sant, D. G.; Tupe, Santosh Genba; Ramana, Chepuri V.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2016)
Increase in invasive fungal infections over the past few years especially in immunocompromised patients prompted the search for new antifungal agents with improved efficacy. Current antifungal armoury includes very few effective drugs like Amphotericin B; new generation azoles, including voriconazole and posaconazole; echinocandins like caspofungin and micafungin to name a few. Azole class of antifungals which target the fungal cell membrane are the first choice of treatment for many years because of their effectiveness. As the fungal cell membrane is predominantly made up of sterols, glycerophospholipids and sphingolipids, the role of lipids in pathogenesis and target identification for improved therapeutics were largely pursued by researchers during the last few years. Present review focuses on cell membrane as an antifungal target with emphasis on membrane biogenesis, structure and function of cell membrane, cell membrane inhibitors, screening assays, recent advances and future prospects.